2019
DOI: 10.1111/mcn.12912
|View full text |Cite
|
Sign up to set email alerts
|

A maternal “mixed, high sugar” dietary pattern is associated with fetal growth

Abstract: This study examined associations between a maternal “mixed, high sugar” dietary pattern during pregnancy and ultrasound‐determined fetal growth in 495 urban African women and explored whether these associations were independent of maternal baseline body mass index (BMI) and gestational weight gain (GWG). Linear mixed effects modelling (LMM) was used to test the associations between maternal mixed, high sugar dietary pattern score, baseline BMI (kg/m2), and GWG (kg/week) and the following fetal growth outcomes:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“… 7 Findings from the Soweto First 1000 Days cohort reported that 67% of women presenting at their first antenatal clinic visit were either overweight or obese. 8 Concerns about obesity also extend to childhood in SA whereby one in four girls age 2 to 14 years, and one in six boys in the same age group, were either overweight or obese. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 Findings from the Soweto First 1000 Days cohort reported that 67% of women presenting at their first antenatal clinic visit were either overweight or obese. 8 Concerns about obesity also extend to childhood in SA whereby one in four girls age 2 to 14 years, and one in six boys in the same age group, were either overweight or obese. 9…”
Section: Introductionmentioning
confidence: 99%
“…7 Findings from the Soweto First 1000 Days cohort reported that 67% of women presenting at their first antenatal clinic visit were either overweight or obese. 8 Concerns about obesity also extend to childhood in SA whereby one in four girls age 2 to 14 years, and one in six boys in the same age group, were either overweight or obese. 9 Given the public health distress around childhood obesity, the SA Medical Research Council, partnering with World Health Organization and the Canadian Institutes of Health Research, launched the Healthy Life Trajectories Initiative (HeLTI) in SA.…”
Section: Introductionmentioning
confidence: 99%
“…8 Data from our longitudinal birth cohort study (Soweto First 1000-Days Study; S1000) has shown that multiple maternal exposures during pregnancy are associated with fetal growth across the prenatal period. [9][10][11] Of all maternal exposures examined in S1000, being at the higher end of the BMI spectrum when entering pregnancy has been most consistently associated with infant outcomes; specifically related to elevated growth across fetal parameters and delivery of larger infants. 11,12 In addition, women who were affected by overweight or obesity at recruitment were more likely to gain excessive weight during pregnancy; with higher GWG also being positively associated with fetal growth and neonatal size.…”
Section: Introductionmentioning
confidence: 99%
“…Participants included men and women aged ≥18 years. Women's FGD were held in three age groups to cover the different stages of the reproductive life course and to potentially avoid older women inhibiting younger women's (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and >40 years) expressions.…”
Section: Data Collectionmentioning
confidence: 99%